2015
DOI: 10.1093/ee/nvv144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CO2and Temperature on Metabolism and Development ofHelicoverpa armigera(Noctuidae: Lepidoptera)

Abstract: Climate change will have a major bearing on survival and development of insects as a result of increase in CO2 and temperature. Therefore, we studied the direct effects of CO2 and temperature on larval development and metabolism in cotton bollworm, Helicoverpa armigera (Hübner). The larvae were reared under a range of CO2 (350, 550, and 750 ppm) and temperature (15, 25, 35, and 45°C) regimes on artificial diet. Elevated CO2 negatively affected the larval survival, larval weight, larval period, pupation, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 51 publications
4
29
2
Order By: Relevance
“…The objectives of the study were to (1) determine the population parameters and consumption rate of H . armigera in response to elevated levels of CO 2 , and compare our life table data with previous life table studies 14–16 ; and (2) predict the fitness of and potential damage caused by H . armigera populations resulting from anticipated future increases in CO 2 concentrations.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…The objectives of the study were to (1) determine the population parameters and consumption rate of H . armigera in response to elevated levels of CO 2 , and compare our life table data with previous life table studies 14–16 ; and (2) predict the fitness of and potential damage caused by H . armigera populations resulting from anticipated future increases in CO 2 concentrations.…”
Section: Introductionmentioning
confidence: 68%
“…Akbar et al . 16 found that CO 2 enrichment and increased temperature increased the consumption and metabolism of H . armigera fed an artificial diet by increasing protease activity and carbohydrates in the midgut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feeding behaviour of the larvae was affected by elevated carbon dioxide. Results showed that elevated carbon dioxide contributed to the increase of food consumption and metabolism of the larvae and this gives an indication that Helicoverpa amigera larvae may cause more damage under elevated carbon dioxide (Akbar et al, 2016). Herlicoverpa amigera is one of the major global insect pest that feed on brassicas and its damage can lead to high yield loss (Machekano et al, 2017).…”
Section: Impact Of Elevated Carbon Dioxide On Insects and Diseasesmentioning
confidence: 99%
“…These pressures from insect pests can either be in a form migration to new areas or they can be in a form of new introduction in areas (Ziska et al, 2016), and these often underlies their distribution and abundance, hence the level of damage they cause to crops (Mazzi & Dion, 2012). Elevated concentrations of carbon dioxide also affect insect pest growth and their development and this often results in changes in the interaction between insect pests and their crop host (Akbar et al, 2016;Elad & Pertot, 2014).…”
Section: Impact Of Elevated Carbon Dioxide On Insects and Diseasesmentioning
confidence: 99%